Donor and acceptor substituted triphenylamines exhibiting bipolar charge-transporting and NLO properties - Gudeika, Dalius; Bundulis, Arturs; Mihailovs, Igors; Volyniuk, Dmytro; Rutkis, Martins; Grazulevicius, Juozas V. (Elsevier Ltd, 2017)
Donor-acceptor type triphenylamine-based malonodinitriles were synthesized and their thermal, optical, photophysical, electrochemical and nonlinear optical properties were studied. The synthesized compounds formed glasses with the glass transition temperatures ranging from 38 to 107 °C. The ionization potentials of the samples of the compounds established by cyclic voltammetry were found to be in the range of 5.50–5.57 eV, while those estimated by photoelectron emission spectrometry ranged from 5.36 to 5.74 eV. The electron affinity values of the compounds were found to be in the range of −3.41–−3.05 eV. The ambipolar charge-transporting properties were observed for the layers of triphenylamine-based malonodinitriles. Hole mobilities of the layers of the compounds were in the range of 10−7–10−6 cm2/V·s, while electron mobilities were by ca. two orders of magnitude higher. All the synthesized compounds had positive sign for second order hyperpolarizability.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Triphenylamine; Malonodinitrile; Glass transition temperature; Ambipolar; Second order hyperpolarizability